Safety and Efficacy of High‐Dose Unfractionated Heparin for Prevention of Venous Thromboembolism in Overweight and Obese Patients. Issue 7 (29th June 2016) - Joy, Mishna; Tharp, Eileen; Hartman, Heather; Schepcoff, Sara; Cortes, Jennifer; Sieg, Adam; Mariski, Mark; Lee, Yeunju; Murphy, Meghan; Ranjbar, Ghazaleh; Sharaf, Sherouk; Yau, Gin; et al.
Abstract : Study Objective: To determine the safety and efficacy of high‐dose subcutaneous unfractionated heparin (UFH) for prevention of venous thromboembolism (VTE) in overweight and obese patients. Design: Single‐center retrospective observational cohort study. Setting: Large academic tertiary care medical center. Patients: A total of 1335 adults who weighed more than 100 kg on admission and received either subcutaneous UFH 7500 units every 8 hours (751 patients [high‐dose group]) or 5000 units every 8 hours (584 patients [low‐dose group]) for VTE prophylaxis during their hospitalization between January 1, 2013, and August 31, 2014. Measurements and Main Results: The incidences of VTE and bleeding complications were assessed in each group. Each group was further divided into four groups based on their body mass index (BMI): overweight (BMI 25–29.9 kg/m 2 ), obese class I (BMI 30–34.9 kg/m 2 ), obese class II (BMI 35–39.9 kg/m 2 ), and obese class III (BMI ≥ 40 kg/m 2 ). The incidence of VTE was similar for patients in the high‐dose group versus those in the low‐dose group for all BMI categories. Bleeding complications were significantly higher for patients in the high‐dose group. The proportion of patients with at least a 2‐g/dl hemoglobin drop from admission was higher in patients in the high‐dose groups in obese classes II and III: obese class II, 46 (30%) of 152 patients in the high‐dose group versus 30 (18%) of 171 patients in the low‐dose group (p<0.01); obese class III, 109 (25%) of 432 patients in the high‐dose group versus 31 (12%) of 249 patients in the low‐dose group (p<0.01). In addition, the proportion of patients who received at least 2 units of packed red blood cell transfusion was significantly higher in patients in the high‐dose group who were in obese class III: 47 (11%) of 432 in the high‐dose group versus 13 (5%) of 249 in the low‐dose group (p<0.01). Conclusion: Administering a higher dose of heparin to patients weighing more than 100 kg may not impart additional efficacy in reducing the incidence of VTE. However, it may increase the risk for bleeding.